Current Approaches in Therapeutic Management of Chronic Neuropathic Pain - Özlem Solak; Vural Kavuncu (Archives of Rheumatology, 2008)
Neuropathic pain is briefly defined as pain caused by a lesion in the nervous system and is common in clinical practice. Pharmacotherapy and neurostimulation therapy are the two most recommended therapies for the treatment of this condition. It is generally accepted that pharmacotherapy remains the mainstay of neuropathic pain management. First-line treatments include gabapentin, 5% lidocaine patch, opioid analgesics, tramadol hydrochloride, and tricyclic antidepressants. Neurostimulation techniques recommended in the treatment of neuropathic pain are transcutaneous electrical nevre stimulation (TENS), peripheral nerve stimulation (PNS), nerve root stimulation (NRS), spinal cord stimulation (SCS), deep brain stimulation (DBS), epidural motor cortex stimulation (MCS) and repetitive transcranial magnetic stimulation (rTMS). Treatment decisions for patients with neuropathic pain can often be difficult. Recently, growing interest in the mechanisms of chronic neuropathic pain has resulted in significant advances in treatment. In this review, recent knowledge on therapeutic management of chronic neuropathic pain is reviewed. (Romatizma 2008; 23: 135-42)